IoT-Driven Business Models : Opportunities and Challenges in Smart Enterprises - Rina Putri; Faisal Harahap; Ade Kusuma (Digital Innovation : International Journal of Management, 2024)
This study investigates how IoT (Internet of Things) technologies enable innovative business models in smart enterprises. By exploring use cases in manufacturing, healthcare, and retail, the research highlights opportunities for operational efficiency and new revenue streams. Challenges related to data management, interoperability, and cybersecurity are also discussed.